(untitled) (Journal of Pakistan Orthopaedic Association, 2026)
Objectives: The purpose of this study was to evaluate the results of tendon transfers in patients with irrepairable radial nerve palsy. Place and Duration of Study: Abbasi Shaheed Hospital from 2006 to 2007 Calender Year Methodology: The study included 15 patients (4 females, 11 males; mean age 28.60 years; range 15 to 55 years) who underwent tendon transfers for radial nerve palsy. Three patients had low and 12 patients had high-level radial nerve palsy. The average followup time was 14.66 months (range 6months to 28months). Results: According to the Chuinard criteria, the results were excellent in two patients (13.33%), good in eight patients (56%), and fair in five patients (33.33%).Two patients (13.33%) had radial deviation deformity and two patients (13.33%) had extension wrist contracture. Conclusion: Treatment of irreparable radial nerve palsy with tendon transfers yields successful results. Radial deviation deformity occurs in patients receiving FCU transfer for finger extension.